2016
DOI: 10.1002/joc.4771
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anthropogenic influence on the intensity of extreme temperatures in China

Abstract: ABSTRACT:The anthropogenic (ANT) influence on the intensity of temperature extremes in China is detected over the period 1958-2012 using the newest homogenized daily observation data set and multi-model simulations from the Coupled Model Intercomparison Project Phase 5 (CMIP5). We applied an optimal fingerprinting method to compare spatial-temporal changes in the intensity of temperature extremes, including annual maxima of daily maximum and daily minimum temperatures (warmest day and night, TXx and TNx) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 30 publications
6
60
1
Order By: Relevance
“…The model-simulated response for TNx appears to be consistent with the observed values across all subregions. Overall, our results support those of previous studies, which demonstrated that models underestimate the changes in TNn and TXn, there is good consistency between the model-simulated and observed values of TNx, and models overestimate the changes in TXx (Zwiers et al 2011;Yin et al 2016;Kim et al 2016). Detection becomes more difficult at low latitudes, perhaps because the region containing available data is too small.…”
Section: Spatial and Temporal Patterns In Observations And Simulationssupporting
confidence: 90%
See 3 more Smart Citations
“…The model-simulated response for TNx appears to be consistent with the observed values across all subregions. Overall, our results support those of previous studies, which demonstrated that models underestimate the changes in TNn and TXn, there is good consistency between the model-simulated and observed values of TNx, and models overestimate the changes in TXx (Zwiers et al 2011;Yin et al 2016;Kim et al 2016). Detection becomes more difficult at low latitudes, perhaps because the region containing available data is too small.…”
Section: Spatial and Temporal Patterns In Observations And Simulationssupporting
confidence: 90%
“…Donat et al (2014 found increasing number of warm days and nights, higher extreme temperature values, shorter cold spell durations and fewer cold days and nights in the Arab regions since the mid-1950s. Increases in warm extremes and decreases in cold extremes have also been observed in Chinese temperature data (You et al 2008(You et al , 2009Yin et al 2016;Lu et al 2016).…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…It has decreased due to anthropogenic influence. This is consistent with earlier findings of Yin et al (2016) and Lu et al (2016), who found that cold extremes in China have decreased due to anthropogenic influence. The recent super cold surge of Eastern China that occurred 21-25 January 2016 would have been much stronger if there was no human-induced warming.…”
Section: Methodssupporting
confidence: 93%